2022
DOI: 10.1002/cbic.202200563
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structural Determination of CmnG‐A, the Adenylation Domain That Activates the Nonproteinogenic Amino Acid Capreomycidine in Capreomycin Biosynthesis

Abstract: Capreomycidine (Cap) is a nonproteinogenic amino acid and building block of nonribosomal peptide (NRP) natural products. We report the formation and activation of Cap in capreomycin biosynthesis. CmnC and CmnD catalyzed hydroxylation and cyclization, respectively, of l-Arg to form l-Cap. l-Cap is then adenylated by CmnG-A before being incorporated into the nonribosomal peptide. The co-crystal structures of CmnG-A with l-Cap and adenosine nucleotides provide insights into the specificity and engineering opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Two isomeric forms currently exist wherein the guanidine moiety is cyclized at either the γ- or β-position of the arginine backbone, creating either the 5-membered enduracididine or 6-membered capreomycidine scaffolds, respectively. Once constructed, enduracididine and capreomycidine ncAAs can be directly incorporated into nonribosomal peptide synthetase (NRPS) products via specific adenylation domain activation, 7 or further transformed by oxidative enzymes 8,9 into other cyclic guanidine-containing natural products. Recent advances have shown that capreomycidines can be divergently biosynthesized on NRPSs via dehydrogenation and thioester-mediated Michael addition reactions in the faulknamycin and muraymycin biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Two isomeric forms currently exist wherein the guanidine moiety is cyclized at either the γ- or β-position of the arginine backbone, creating either the 5-membered enduracididine or 6-membered capreomycidine scaffolds, respectively. Once constructed, enduracididine and capreomycidine ncAAs can be directly incorporated into nonribosomal peptide synthetase (NRPS) products via specific adenylation domain activation, 7 or further transformed by oxidative enzymes 8,9 into other cyclic guanidine-containing natural products. Recent advances have shown that capreomycidines can be divergently biosynthesized on NRPSs via dehydrogenation and thioester-mediated Michael addition reactions in the faulknamycin and muraymycin biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Two isomeric forms currently exist wherein the guanidine moiety is cyclized at either the γ- or β-position of the arginine backbone, creating either the five-membered enduracididine or six-membered capreomycidine scaffolds, respectively. Once constructed, enduracididine and capreomycidine ncAAs can be directly incorporated into nonribosomal peptide synthetase (NRPS) products via specific adenylation domain activation or further transformed by oxidative enzymes , into other cyclic guanidine-containing natural products. Recent advances have shown that capreomycidines can be divergently biosynthesized on NRPSs via dehydrogenation and thioester-mediated Michael addition reactions in the faulknamycin and muraymycin biosynthetic pathways. , …”
Section: Introductionmentioning
confidence: 99%